The mechanical performance of pultruded composite rods with embedded fiber-optic sensors - Kalamkarov, Alexander L.; Fitzgerald, Stephen B.; Georgiades, Tasos (My University, 2000)
Fiber-optic strain sensors are successfully embedded in glass- and carbon-fiber-reinforced polymer (GFRP and CFRP) tendons during pultrusion. The study of the performance of the embedded Fabry-Perot fiber-optic sensors under conditions of static and dynamic loading when exposed to both low and high temperature extremes, is presented. The experiments entailed subjecting the GFRP and CFRP tendons to sinusoidal and trapezoidal load waveforms of about 11 kN magnitude inside a temperature chamber. The temperature in the chamber was varied from -40 to 60°C in increments of 20°C. The strain output from the embedded sensors was compared to that from externally mounted extensometers as well as to theoretical strain values. It was determined that the performance of the Fabry-Perot sensors was not affected by ambient temperatures falling within the range of -40 to +60°C and the sensor readings conformed very well with the corresponding extensometer and theoretical readings.
Keywords: Optical fiber detectors; Pultrusion; Strain gages